2018
DOI: 10.4314/sajas.v48i1.18
|View full text |Cite
|
Sign up to set email alerts
|

The influence of different dietary energy concentrations on the production parameters of feedlot ostriches

Abstract: Energy is essential for the continuous survival of any living organism. In ostrich diets, energy is usually derived from maize, which is often subject to fluctuations in yield as a result of drought conditions. Therefore, the optimal utilization of energy in the diets of ostriches becomes of paramount importance, but without affecting the performance of the birds negatively. This study was conducted to investigate the influence of five treatment diets, each with a different energy concentration, on the growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…A description of average feed intake per bird per day of each feeding regime at the growth phase is presented in Table 3 . It is evident that the average feed intake increases with the growth phase, as can be expected with increase in size of the ostrich chicks (Brand et al, 2018b , 2019 ). The energy level of the diet was found to influence the average intake in the pre-starter, grower and finisher phases, with feed intake decreasing from the low- to high-energy regimes ( p < 0.05).…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…A description of average feed intake per bird per day of each feeding regime at the growth phase is presented in Table 3 . It is evident that the average feed intake increases with the growth phase, as can be expected with increase in size of the ostrich chicks (Brand et al, 2018b , 2019 ). The energy level of the diet was found to influence the average intake in the pre-starter, grower and finisher phases, with feed intake decreasing from the low- to high-energy regimes ( p < 0.05).…”
Section: Resultsmentioning
confidence: 60%
“…This is supported by the popular belief that monogastric animals will eat to fulfil their energy requirements (McDonald et al 2002 ; Schinckel & De Lange 1996 ). Brand et al ( 2018b ) also demonstrated the relationship of intake in ostriches decreasing in response to higher dietary energy densities. The higher rates of increase in EBPW in ostriches reared on low-energy diets, along with the higher intakes, suggest that the birds consumed greater quantities of protein, which can be used for enhanced growth.…”
Section: Discussionmentioning
confidence: 94%